2021
DOI: 10.17509/ijost.v6i3.38951
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study and Theoretical Comparison of Outlet Hole Geometry for a Gravitational Vortex Turbine

Abstract: The gravitational water vortex turbine is an alternative to renewable energies, it transforms the hydrokinetic energy of the rivers into electric energy and it does not require a reservoir. According to studies carried out, the hydraulic efficiency can increase or decrease according to the turbine geometrical configuration. This paper presents a numerical (CFD) and analytical comparison between conical and cylindrical designs for the outlet. The results show a higher performance for conical geometry than the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…According to the results, the H-Darrieus rotor works with increasing lift force [22,35]. However, the rotor inside the GVT interacts with drag and not lift force [36], which does not allow a better performance of this rotor. It must be considered that the area of the blade face perpendicular to the fluid is less than that of the conventional rotor (straight blades); therefore, this also directly influences the performance of the GVT given that the greater the contact area of the fluid with the rotor, the drag force on the rotor increases.…”
Section: Fig 7 Generated Torque Vs Angular Velocity In Gvtmentioning
confidence: 94%
“…According to the results, the H-Darrieus rotor works with increasing lift force [22,35]. However, the rotor inside the GVT interacts with drag and not lift force [36], which does not allow a better performance of this rotor. It must be considered that the area of the blade face perpendicular to the fluid is less than that of the conventional rotor (straight blades); therefore, this also directly influences the performance of the GVT given that the greater the contact area of the fluid with the rotor, the drag force on the rotor increases.…”
Section: Fig 7 Generated Torque Vs Angular Velocity In Gvtmentioning
confidence: 94%
“…For this reason, the Swiss turbine stands out for being the largest power generator at a lower flow rate and height. It is also worth noting that between Italy, Austria, and Germany they have seven (7) installed turbines, demonstrating the superiority in GVT installed. To exemplify Table 2, the calculation of the electrical power of (1) [1] was taken.…”
Section: Gvt Installedmentioning
confidence: 95%
“…The findings showed that the concave basin system outperformed the convex basin system, producing power outputs of 0.37 W and 0.23 W, respectively. Additionally, Sánchez et al [58] compared a GWVHT system with a conical basin to one with a cylindrical basin in terms of discharge hole size. The results indicated that the conical basin system performed better than the cylindrical basin system.…”
Section: Non-parametric Studies On Basins and Channelsmentioning
confidence: 99%